Application of Histogram Equalization for Image Enhancement in Corrosion Areas - Jianbin Xiong; Dezheng Yu; Qi Wang; Lei Shu; Jian Cen; Qiong Liang; Huanyang Chen; Baocheng Sun (Shock and Vibration)
In this paper, an image enhancement algorithm is presented for identification of corrosion areas and dealing with low contrast present in shadow areas of an image. This algorithm uses histogram equalization processing under the hue-saturation-intensity model. First of all, an etched image is transformed from red-green-blue color space to hue-saturation-intensity color space, and only the luminance component is enhanced. Then, part of the enhanced image is combined with the original tone component, followed by saturation and conversion to red-green-blue color space to obtain the enhanced corrosion image. Experimental results show that the proposed method significantly improves overall brightness, increases contrast details in shadow areas, and strengthens identification of corrosion areas in the image.